Pengaruh Brand Ambassador, Brand Personality Dan Korean Wave Terhadap Keputusan Pembelian Produk Nature Republic Aloe Vera - Ayu Sagia; Syafrizal Helmi Situmorang (Forum Manajemen Indonesia (FMI), 2018)
This study aims to determine the impact of Brand Ambassador, Brand Personality and Korean Wave toward Purchase Decision Nature Republic Aloe Vera skincare product in the Faculty of Culture University Sumatera Utara. This research is associative research and the type of data used is quantitative data. The population of this research is students in the Faculty of culture University Sumatera Utara. The sample in this study amounted to 92 respondent. The technique used is multiple linear regressions. The results of this study showed that Brand Ambassador, Brand Personality and Korean Wave simultaneously, significantly influence towards purchase decision Nature Republic Aloe Vera skincare product in the Faculty of Culture University Sumatera Utara. Partially, Brand Ambassador has a positive and significant effect to purchase decision, Brand Personality has a positive and significant effect to purchase decision, Korean Wave has a positive and significant effect to purchase decision Nature Republic Aloe Vera skincare product in the Faculty of Culture University Sumatera Utara. Keywords: Brand Ambassador, Brand Personality, Korean Wave, Purchase Decision